Characterization of Epileptic Spiking Associated With Brain Amyloidosis in APP/PS1 Mice - Gureviciene, Irina; Ishchenko, Irina; Ziyatdinova, Sofya; Jin, Nanxiang; Lipponen, Arto; Gurevicius, Kestutis; Tanila, Heikki (Frontiers in Neurology, 2019)
Epileptic activity without visible convulsions is common in Alzheimer’s disease (AD) and may contribute adversely to the disease progress and symptoms. Transgenic mice with amyloid plaque pathology also display epileptic seizures, but those are too infrequent to assess the effect of anti-epileptic treatments. Besides spontaneous seizures, these mice also display frequent epileptic spiking in epidural EEG recordings, and these have provided a means to test potential drug treatment to AD-related epilepsy. However, the origin of EEG spikes in transgenic AD model mice has remained elusive, which makes it difficult to relate electrophysiology with underlying pathology at the cellular and molecular level. Using multiple cortical and subcortical electrodes in freely moving APP/PS1 transgenic mice and their wild-type littermates, we identified several types of epileptic spikes among over 15 800 spikes visible with cortical screw electrodes based on their source localization. Cortical spikes associated with muscle twitches, cortico-hippocampal spikes, and spindle and fast-spindle associated spikes were present equally often in both APP/PS1 and wild-type mice, whereas pure cortical spikes were slightly more common in APP/PS1 mice. In contrast, spike-wave discharges, cortico-hippocampal spikes with afterhyperpolarization and giant spikes were seen almost exclusively in APP/PS1 mice but only in a subset of them. Interestingly, different subtypes of spikes responded differently to anti-epileptic drugs ethosuximide and levetiracetam. From the translational point most relevant may be the giant spikes generated in the hippocampus that reached an amplitude up to +/- 5 mV in the hippocampal channel. As in AD patients, they occurred exclusively during sleep. Further, we could demonstrate that a high number of giant spikes in APP/PS1 mice predicts seizures. These data show that by only adding a pair of hippocampal deep electrodes and EMG to routine cortical epidural screw electrodes and by taking into account underlying cortical oscillations, one can drastically refine the analysis of cortical spike data. This new approach provides a powerful tool to preclinical testing of potential new treatment options for AD related epilepsy.